Blindness Caused by Traumatic Optic Neuropathy and Central Retinal Artery Occlusion after Endoscopic Sinus Surgery: A Case Report - Zafer Öztaş (Türk Oftalmoloji Dergisi, 2015)
Herein, we report the case of a patient who developed unilateral blindness secondary to traumatic optic neuropathy and central retinal artery occlusion (CRAO) after endoscopic sinus surgery (ESS). Visual acuity was no light perception in the right eye and 1.0 in the left eye. Antrerior segment was normal in both eyes. Fundoscopy revealed pallor white coloration of the macula with indistinct margins of the optic disc in the right eye and normal in the left eye. Fundus fluorescein angiography demonstrated CRAO. Fracture lines of the orbital wall at the level of the anterior ethmoidal cells and pronounced deviated nasal septum were detected on computed tomography. Herniation of the medial and inferior rectus muscles with extraconal fat tissue was observed. In addition to the findings on computed tomography, magnetic resonance imaging of the orbita showed signal changes in the optic nerve and retrobulbar edema indicating traumatic optic neuropathy. In order to prevent severe vision loss, the surgeon should repair deviated nasal septum before the ESS and must pay serious attention during the operation. (Turk J Ophthalmol 2015; 45: 42-44)